2013
DOI: 10.1371/journal.pone.0071340
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Analysis of the Binding Modes and Binding Affinities of Small Molecule Modulators of PDZ-Peptide Interactions

Abstract: Inhibitors of PDZ-peptide interactions have important implications in a variety of biological processes including treatment of cancer and Parkinson’s disease. Even though experimental studies have reported characterization of peptidomimetic inhibitors of PDZ-peptide interactions, the binding modes for most of them have not been characterized by structural studies. In this study we have attempted to understand the structural basis of the small molecule-PDZ interactions by in silico analysis of the binding modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…It was earlier reported that when flexibilities are introduced into the protein and ligand, the computed binding energy values show better correlation with experimental results [34]. Thus, the MM-BSA binding free energy value, G bind = −12.27calculated for andrographolide within the binding site of 1M4I after MD simulation revealed that 1M4I could be a probable target protein for andrographolide.…”
Section: Stability Of the Andrographolide Target Complex By MD Simulamentioning
confidence: 67%
“…It was earlier reported that when flexibilities are introduced into the protein and ligand, the computed binding energy values show better correlation with experimental results [34]. Thus, the MM-BSA binding free energy value, G bind = −12.27calculated for andrographolide within the binding site of 1M4I after MD simulation revealed that 1M4I could be a probable target protein for andrographolide.…”
Section: Stability Of the Andrographolide Target Complex By MD Simulamentioning
confidence: 67%
“…Docking was then carried out by using PEP-FOLD3 18 and I-TASSER 20 to model the structure of peptide and antigen. PyRx of AutoDock Vina docking software was used to predict binding energies and root-mean-square deviations (RMSD) 21 , 22 . PyMOL Molecular Graphics System was used to visualize interactive residues between peptides and antigen 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is evident that the bond length or angle of the noncritical part of the ligand structure can be fixed (Morris et al, 2015). Semi-flexible docking is suitable for the docking of small molecules and macromolecules, such as proteins or nucleic acids and small ligand molecules (Tiwari & Mohanty, 2013;Jiang et al, 2016). It takes into account the influence of changes on the ligand structure and can be employed in a broader range of applications.…”
Section: Semi-flexible Dockingmentioning
confidence: 99%